2014
DOI: 10.1177/0049085714536802
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Traditional Agricultural Knowledge in Delta State, Nigeria

Abstract: Many sustainable agricultural practices that emanate from local and traditional farming knowledge and are environment friendly in the face of climate change are steadily being abandoned. These practices include the use of manure, local weather forecast and planting of various local cassava varieties to manage risk. This study examines the characteristics of those who maintain these traditional practices to ascertain if the maintenance of these local agricultural practices can be explained by adoption diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The higher the level of poultry farmers' formal education is, the more the likelihood of practicing the integration poultry-vegetable farming. This, according to Ofuoku and Albert (2014) is for the reason that education raises one's ability and attitude to inquire into the advantages associated with an innovation or idea. Madukwe (1995) suggests that education is one of the salient variables of adoption of farm practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the level of poultry farmers' formal education is, the more the likelihood of practicing the integration poultry-vegetable farming. This, according to Ofuoku and Albert (2014) is for the reason that education raises one's ability and attitude to inquire into the advantages associated with an innovation or idea. Madukwe (1995) suggests that education is one of the salient variables of adoption of farm practices.…”
Section: Discussionmentioning
confidence: 99%
“…Male poultry farmers are more likely to practice integration of poultry with vegetable farming. Ofuoku (2014) found that poultry farming in Delta State, Nigeria is male dominated. The male poultry farmers being household heads are more likely to practice the integrated farming in order to earn extra income and food source to cater for their households which form part of their responsibilities to their families.…”
Section: Discussionmentioning
confidence: 99%
“…In the MMT, the farmers were requested to give their local perceptions about alterations in climate based on their experiences and observations of alterations/variations in climate parameters such as rainfall and temperature. Ethnographic studies have the confirmation that persons are capable of identifying change in climate a decade or more on the basis of his or her own experience (Ofuoku and Albert, 2014;Marin, 2010). A previous study by Ofuoku et al (2012) saw through the lenses of the farmers and found that the farmers identified alterations in climate parameters such as rainfall and temperature for over a period of 30 years.…”
Section: Design Of the Questionnairementioning
confidence: 97%
“…In the MMT, the farmers were requested to give their local perceptions about alterations in climate based on their experiences and observations of alterations/variations in climate parameters. Ethnographic studies have the con rmation that persons are capable of identifying change in climate a decade or more on the basis of his or her own experience (Ofuoku and Albert, 2014;Marin, 2010). A previous study by Ofuoke et al (2012) saw through the lenses of the farmers and found that the farmers identi ed alterations in climate parameters such as rainfall and temperature for over a period of 30 years.…”
Section: Design Of the Questionnairementioning
confidence: 99%